2003
DOI: 10.1002/anie.200351209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acyloxyphosphonium Ions and the Stereochemical Influence of Base in the Phosphorane‐Mediated Esterification of Alcohols

Abstract: The Mitsunobu reaction [1][2][3][4] is widely employed in both condensation and displacement reactions of alcohols with various nucleophiles and normally proceeds with inversion of stereochemistry when chiral secondary alcohols are used. The mechanism of the reaction continues to receive attention and the present view is summarized in Scheme 1. Although the [*] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…[81] Evidence for direct acylation and a basemediated crossover step under both neutral and basic conditions has been provided. [82] Additional insights into the formation of pentacoordinate phosphorus intermediates have been furnished by 31 P NMR spectroscopy. [78,83,84] The general mechanism for the Mitsunobu reaction is outlined in Figure 8.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…[81] Evidence for direct acylation and a basemediated crossover step under both neutral and basic conditions has been provided. [82] Additional insights into the formation of pentacoordinate phosphorus intermediates have been furnished by 31 P NMR spectroscopy. [78,83,84] The general mechanism for the Mitsunobu reaction is outlined in Figure 8.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Such basic species would be expected to promote the ''cross-over'' step resulting in the formation of 4 leading to the inversion product. This hypothesis was supported by the unambiguous independent generation of acyloxyphosphonium ions [9] and trapping with chiral secondary alcohols under neutral or basic conditions where high levels of retention or inversion of stereochemistry were observed respectively.…”
mentioning
confidence: 88%
“…These results show that the nature of any basic species present or generated in the reaction can have a profound effect on the stereochemistry of esterification using Mitsunobu or related procedures. 544 In N-alkylation reactions promoted by tertiary phosphine-azoester reagents, it has been shown that use of a phosphine more bulky than trimethylphosphine gives a high intramolecular selectivity between primary and secondary alcohol groups. Thus, trimethylphosphine is the only phosphine that enables alkylation of 2-nitrobenzenesulfonamides with a wide range of secondary alcohols, whereas tributylphosphine is selective for primary alcohol groups.…”
Section: Nucleophilic Attack At Other Atomsmentioning
confidence: 99%